Development of novel bioadhesive granisetron hydrochloride spanlastic gel and insert for brain targeting and study their effects on rats - Rehab Abdelmonem; Mohamed el Nabarawi; Alshaimaa Attia (Drug Delivery, 2018)
The aim of this study was to formulate granisetron hydrochloride (GH) spanlastic in mucoadhesive gels and lyophilized inserts for intranasal administration to improve GH bioavailability and brain targeting. Carpapol 934 and HPMC were incorporated in GH spanlastic in nasal gels (GHSpNGs). Gelatin and HPMC as matrix former, glycine as a collapse protecting and mannitol as an insert filler and sweeting agent were used to prepare GH spanlastic loaded in lyophilized inserts (GHSpNIs). The prepared GHSpNGs were characterized for pH measurement, drug content, rheology, and in vitro drug release. The prepared GHSpNIs were characterized for drug content, surface pH, GH release, and mucoadhesion. Biological investigations including pharmacokinetics studies and brain drug targeting efficiency dimensions were performed on rats (LC–MS/MS). The results showed thixotropic pseudoplastic gels and white insert with pH values in a physiological range, drug content (89.9–98.6%), (82.4–98.38%) for gel and insert, respectively and rapid release rate of GH. Biological studies showed that Cmax and AUC0–6 h in brain and plasma after intranasal administration of gel and insert were higher compared to IV administration of GH solution. A high brain targeting efficiency (199.3%, 230%) for gel and insert, respectively and a direct nose to brain transport (49.8%, 56.95%) for gel and insert, respectively confirmed that there is a direct nose to brain transport of GH following nasal administration of GH spanlastic loaded in nasal gel and insert. GHSpNIs can be considered as potential novel drug delivery system intended for brain targeting via the nasal rout of administration than GHSpNGs.